Public knowledge of blood cancers - Gieniec, Weronika; Gucwa, Magdalena; Galus, Adrian; Jurkiewicz, Beata (Journal of Education, Health and Sport, 2022)
Introduction. Blood cancers are a group of conditions that develop in the bone marrow and/or lymphatic system and include cancers of the hematopoietic system and cancers of the lymphatic system. The key test for blood cancers diagnosing is complete blood count. The aim of the study was to assess the level of public knowledge about blood cancers and their treatment. The study was conducted in March 2022 by a diagnostic survey method using a proprietary survey questionnaire made available online via Google Forms. The analysis included 311 correctly completed questionnaires. Results and conclusions. The respondents’ level of knowledge about blood cancers and their treatment methods is very low. Nearly half of the respondents perform blood counts too infrequently (every two years or less often). Those with any knowledge of blood cancers (defined as minimal in the knowledge test) performed a blood count every six months, and not less often than once a year. Nearly 1/3 of the respondents do not want to donate bone marrow because they are afraid of the procedure. Of those registered or those who attempted registration, most presented a level of knowledge defined as minimal. The vast majority of respondents would like to see more events to promote blood cancer awareness.